In Situ Capping Remediation of Contaminated Marine Sediment using Bentonite, Kaolin and Sand to Interrupt the Release of Trace Metals - Aliyu, Mohammed Kabir; Ahmad Tarmizi Abd. Karim,; Ming Chan, Chee (International Journal of Sustainable Construction Engineering and Technology, 2020)
In situ capping remediation is a technique by which a capping material is placed on top of sediments to prevent continued contamination of surface water from the contaminated sediments. In this study Bentonite, Kaolin, Sand and mixture of Bentonite with Kaolin were used as capping materials. The objective of this study was to investigate the possibility of using Bentonite, kaolin, mixture of Bentonite with kaolin (1:1) and sand as capping materials to block the release of trace metals (Pb, Cd, Cr, Cu, and Zn) from the artificially contaminated marine sediments, A bench scale laboratory experiment in aquariums was performed for a period of 90 days where 1-cm-thick layer of capping materials was placed above the contaminated sediments. The average Pb concentration in control, capped with bentonite, kaolin, and mixture of both is 4.08, 0.77, 6.77and 0.84mg/l respectively, similarly for Cr is 5.63, 0.15, 5.63 and 0.29 mg/l respectively. The average concentration for Cu is 4.28, 0.145, 5.63 and 0.11mg/l respectively and also for Zn and Cd which are the most mobile is 68.81, 5.82, 75.56 and 23.46 mg/l and 58.35, 14.75, 59.97 and 39.8 mg/l respectively. The trace metals were released into the overlying water from the heavily contaminated sediments in the following decreasing order Cd > Zn > Cu > Pb > Cr. For the uncapped all the contaminants are constantly released with various kinetic depending of mineral oxidation or dissolution or leaching. The release did not go beyond 32 % of the initial pollutants in the sediments. Bentonite and its mixture with Kaolin have much higher metal adsorption capacity compared to that of only Kaolin. The results showed that the capping materials Bentonite and mixture of Bentonite with Kaolin were effective in interrupting the release of Pb, Cu and Cr throughout the experimental period but Cd and Zn were only captured from the beginning but later released gradually until completion. It was concluded that Bentonite and its mixture additive can be used as potential capping materials for the remediation of contaminated sites.